A comprehensive mechanistic model of iron metabolism in Saccharomyces cerevisiae. Issue 11 (18th September 2019) - Lindahl, Paul A.
Abstract : The ironome of budding yeast ( circa 2019) consists of approximately 139 proteins and 5 nonproteinaceous species. Abstract : The ironome of budding yeast ( circa 2019) consists of approximately 139 proteins and 5 nonproteinaceous species. These proteins were grouped according to location in the cell, type of iron center(s), and cellular function. The resulting 27 groups were used, along with an additional 13 nonprotein components, to develop a mesoscale mechanistic model that describes the import, trafficking, metallation, and regulation of iron within growing yeast cells. The model was designed to be simultaneously mutually autocatalytic and mutually autoinhibitory – a property called autocatinhibitory that should be most realistic for simulating cellular biochemical processes. The model was assessed at the systems' level. General conclusions are presented, including a new perspective on understanding regulatory mechanisms in cellular systems. Some unsettled issues are described. This model, once fully developed, has the potential to mimic the phenotype (at a coarse-grain level) of all iron-related genetic mutations in this simple and well-studied eukaryote.